A diagnostic approach for neurodegeneration with brain iron accumulation: clinical features, genetics and brain imaging - Rubens Paulo Araújo Salomão; José Luiz Pedroso; Maria Thereza Drumond Gama; Lívia Almeida Dutra; Ricardo Horta Maciel; Clécio Godeiro-Junior; Hsin Fen Chien; Hélio A. G. Teive; Francisco Cardoso; Orlando G. P. Barsottini (Arquivos de Neuro-Psiquiatria, 2016)
ABSTRACT Neurodegeneration with brain iron accumulation (NBIA) represents a heterogeneous and complex group of inherited neurodegenerative diseases, characterized by excessive iron accumulation, particularly in the basal ganglia. Common clinical features of NBIA include movement disorders, particularly parkinsonism and dystonia, cognitive dysfunction, pyramidal signs, and retinal abnormalities. The forms of NBIA described to date include pantothenase kinase-associated neurodegeneration (PKAN), phospholipase A2 associated neurodegeneration (PLAN), neuroferritinopathy, aceruloplasminemia, beta-propeller protein-associated neurodegeneration (BPAN), Kufor-Rakeb syndrome, mitochondrial membrane protein-associated neurodegeneration (MPAN), fatty acid hydroxylase-associated neurodegeneration (FAHN), coenzyme A synthase protein-associated neurodegeneration (CoPAN) and Woodhouse-Sakati syndrome. This review is a diagnostic approach for NBIA cases, from clinical features and brain imaging findings to the genetic etiology.